Optimism, parental social support, and academic achievement in english language learning: Exploring the interconnetions - Sudirman, Subhan Ajrin; Yusri, Nur 'Aisyiah; Yuharnida, Yuharnida (Al-Qalb : Jurnal Psikologi Islam, 2024)
This research aims to investigate the relationship between optimism and parental social support concerning students' academic achievement in English language learning. A psychological approach is employed in this study to comprehend how psychological factors such as optimism and parental social support can influence students' academic attainment in English. A quantitative research method involving 317 high school students as research subjects is utilized. The research findings reveal a positive correlation between students' level of optimism and their academic achievement in English language learning. Students with higher levels of optimism tend to attain better academic performance in English. Furthermore, the social support provided by parents is also found to have a positive association with students' academic achievement in English. Students who feel emotionally and practically supported by their parents tend to achieve higher scores in the English subject. This study also underscores the importance of psychological factors such as optimism and parental social support in enhancing students' academic achievement in English. The practical implications of these findings highlight the significance of emotionally supporting students and providing concrete support in the process of English language learning. Educators and parents can play an active role in motivating students and creating a supportive environment to enhance students' academic achievement in English. This research also contributes significantly to understanding the factors influencing students' academic achievement in English language learning and provides guidance for the development of effective intervention strategies in educational contexts.